Ninth Five Year Plan 1997-2002 Volume I Development Goals, Strategy and Policies - Planning Commission, Government of India (Planning Commission, Government of India, 1997)
The Ninth Five Year Plan, launched in the 50th year of India’s Independence, will take the country into the new millennium. Much has happened in the fifty years since independence. The people of India have conclusively demonstrated their ability to forge a nation united despite its diversity, and their commitment to pursue development within the framework of a functioning, vibrant and highly pluralistic democracy. In this process democratic institutions have put down firm roots and flourished and development has also taken place on a wide front.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Ninth Five Year Plan- India; Development Goals, Strategy and Policies; Economic development in India